Faktor-Faktor Risiko Pasien Diabetes Melitus - Zahtamal Fifia Chandra, Suyanto, Tuti Restuastuti (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Diabetes Mellitus (DM) remains a health problem in Indonesia as well as in many other countries. According to Medical Record of Regional Hospital of Arifin Achmad Riau Province, the incidence of DM still high among endocrine, nutrition and metabolic diseases. About 188 cases of DM had recorded in the year 2003, 221 case in the year 2004 and 158 case in 2005. One of the strategies to decrease and manage this disease is by the screening risk factors besides an adequate therapy.Objective: To assess the risk factors for DM such as age, family history of diabetes, dietary habits, knowledge about DM and type of personality amongst patient with DM.Methods: A case-control study was conducted on 154 patient from Regional Hospital of Arifin Achmad Riau Province. Cases included 79 patient identified as a DM and controls include 75 patient who did not suffer DM. Data of age, family history of diabetes, dietary habits and type of personality was taken by questionnaire diabetes risk factors. Data of risk factors was obtained by a questionnaire given to 2 groups (case and control group).Results: There was association between several risk factors and incidence of DM, include; age [odds ratio (OR) = 6, 45; p= 0,000, PAR= 0, 84], family history of DM (OR= 3, 75; p = 0,001, PAR= 0, 73), knowledge about DM (OR= 0, 13; p = 0,000, PAR= -6, 7/as a protective factor). However, there was evidence of a no association between type of personality and incidence of DM (OR= 50.4; p = 0,479, PAR= 0, 98) and also dietary habits (OR= 1, 06; p = 0,896, PAR= 0 06)Conclusion: These findings suggest a complex interaction among age factor, family history of diabetes, knowledge about DM, dietary habits and type of personality with the incidence of DM in Regional Hospital of Arifin Achmad Riau Province.Keywords: risk factors, diabetes mellitus, type of personality